2019
DOI: 10.1007/s00228-019-02624-1
|View full text |Cite
|
Sign up to set email alerts
|

Can screening tools for potentially inappropriate prescriptions in older adults prevent serious adverse drug events?

Abstract: Purpose The purpose of the study is to identify and explore risk factors of serious adverse drug events (SADE) and SADE-related admissions in acutely hospitalized multimorbid older adults and assess whether these could have been prevented by adherence to the prescription tools Screening Tool of Older Persons' Prescriptions (STOPP) and The Norwegian General Practice (NORGEP) criteria. Methods Cross-sectional study of acutely admitted patients to a medical department in a Norwegian regional hospital. Eligible pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…As with all register-based studies, one cannot conclude if PIMs have led to actual drug-related problems for the patients. A recent study looking at patients with multimorbidity acutely admitted to the hospital, found that strict adherence to the NORGEP-criteria could have prevented 15% of the serious adverse drug reactions [44]. The NORGEP-criteria was published in 2009.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As with all register-based studies, one cannot conclude if PIMs have led to actual drug-related problems for the patients. A recent study looking at patients with multimorbidity acutely admitted to the hospital, found that strict adherence to the NORGEP-criteria could have prevented 15% of the serious adverse drug reactions [44]. The NORGEP-criteria was published in 2009.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Approximately 50% of MEs result in adverse drug events (ADEs) causing significant increase in patient morbidity and mortality as well as in economic costs in health care (Hohl et al, 2001;Krähenbühl-Melcher et al, 2007;Alhawassi et al, 2014;Classen et al, 2016;Walsh et al, 2017). As ADEs caused by MEs are generally considered preventable, understanding MEs is particularly important when developing and improving preventative methods towards medication-related patient harm (Morimoto et al, 2004;Asaad Assiri et al, 2018;Wang-Hansen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Frailty has been shown to be associated with higher mortality, longer in-hospital stay and more complications, also in individuals without multimorbidity (19,21,43). Moreover, previous studies have found multimorbidity (3), polypharmacy (5,44), functional decline 7, low handgrip strength (20), sarcopenia (18,45) and cognitive decline (8) to be associated with one-year mortality. None of these frailty indicators were associated with one-year mortality in our study population.…”
Section: Discussionmentioning
confidence: 99%